Drivers of Firn Density on the Greenland Ice Sheet Revealed by Weather Station Observations and Modeling. Issue 10 (24th October 2018) - Vandecrux, B.; Fausto, R. S.; Langen, P. L.; van As, D.; MacFerrin, M.; Colgan, W. T.; Ingeman‐Nielsen, T.; Steffen, K.; Jensen, N. S.; Møller, M. T.; Box, J. E.
Abstract: Recent Arctic atmospheric warming induces more frequent surface melt in the accumulation area of the Greenland ice sheet. This increased melting modifies the near‐surface firn structure and density and may reduce the firn's capacity to retain meltwater. Yet few long‐term observational records are available to determine the evolution and drivers of firn density. In this study, we compile and gap‐fill Greenland Climate Network (GC‐Net) automatic weather station data from Crawford Point, Dye‐2, NASA‐SE, and Summit between 1998 and 2015. These records then force a coupled surface energy balance and firn evolution model. We find at all sites except Summit that increasing summer turbulent heat fluxes to the surface are compensated by decreasing net radiative fluxes. After evaluating the model against firn cores, we find that, starting from 2006, the density of the top 20 m of firn at Dye‐2 increased by 11%, decreasing the pore volume by 18%. Crawford Point and Summit show stable near‐surface firn density over 1998–2010 and 2000–2015 respectively, while we calculate a 4% decrease of firn density at NASA‐SE over 1998–2015. For each year, the model identifies the drivers of density change in the top 20‐m firn and quantifies their contributions. The key driver, snowfall, explains alone 72 to 92% of the variance in day‐to‐day change in firn density while melt explains from 7 to 33%. Our result indicates that correct estimates of the magnitude and variability of precipitation are necessary to interpret or simulate the evolution of the firn. Plain Language Summary: Arctic warming has led to more intense melt on the Greenland ice sheet. In recent decades this melt moved upglacier and started to alter the structure of perennial snow, or firn, in areas where melt was rarely recorded. In this study, we process 12–17 years of observations from four weather stations located in the vast high‐elevation area of the ice sheet. From these climate records, we calculate how much melt occurred each summer and why (e.g., warm air or sunlight absorption). We found that heat transfer from the air to the surface has become more intense but is compensated by a brightening of the surface, causing less sunlight to be absorbed and used for melting. We use a computer model that simulates firn evolution and shows a good match with independent observations of the firn density. Our simulations identify increasing firn density at a first site, stable density at two sites, and decreasing firn density at the last one. Day‐to‐day and year‐to‐year changes in the density of the top 20 m of firn were mostly due to the snowfall variability followed by surface melt. This work underlines the importance of accurate precipitation estimates in order to understand firn evolution. Key Points: We gathered, processed, and gap‐filled underexploited climate observations at four sites from the Greenland ice sheet accumulation area Increasing turbulent heat fluxes were found at three sites over the 1998–2015 period, compensated by decreasing net radiative fluxes Our simulation of near‐surface firn density quantifies the role of its climatic drivers among which snowfall and surface melt are dominant